An efficient and scalable coordinating algorithm for distributed network intrusion detection system - Tewapong Wongkhuenkaew (2018)
© 2015 IEEE. Intrusion detection systems can be deployed for detecting distributed denied-of-service attack. However, because of the scale of the attack and/or size of the managed network, distributed intrusion detection system is more suitable than a centralized one. Nevertheless, because of distributed nature of such system, network traffic overhead and scalability become problem. This paper proposes a tree-based coordination algorithm for distributed intrusion detection system which is efficient, in terms of traffic overhead, and also scalable. The experimental results confirm that this approach allows intrusion detection system to scale and efficient to the number of detectors.